The unmet need of psycho-oncology services for integrated cancer care in India: a review - Brahmbhatt, Twinkle; Gunjan Desai (International Journal Of Community Medicine And Public Health, 2023)
Cancer has varied effects on mental health of the patients, their family and friends as well as the caregivers. The emotional, social, interpersonal, rehabilitative and psychological effects of cancer on all of them can contribute to psycho-social distress. Appropriately addressing psychological, social and behavioral issues through psycho-oncology services improves the physician-patient relationship, increase satisfaction to the ongoing treatment, create a positive attitude towards treatment and outcomes and improve the quality of life. It also has a role in preventive oncology as well as in cancer rehabilitation. Global recognition of the need of psycho-oncology services has led to establishment of a lot of international organizations and societies in the developed countries. On the other hand, there are no societies or standard guidelines for psychosocial care in India. Also, due to lack of awareness and cancer education, the stigma associated with this care compounded by the stigma associated with cancer is a major hindrance to availing mental health care in India. Identifying this unmet need, creating awareness about the need of distress management during key transitions in cancer care pathway and providing training and research opportunities in this field in India will pave the way to improve the outcomes of cancer treatment delivery and patient compliance as well as satisfaction to the provided care. Psycho-oncology services need to be integrated into the existing cancer care pathways in a structured manner so as to enable ease of availability of these services for the patients and their families when in need.